Inovasi dan Daya Saing UMKM di Era New Normal: dari Triple Helix Model ke Quadruple Helix Model - Umu Khouroh; Christina Sri Ratnaningsih; Bayu Rahayudi (Jurnal Manajemen dan Kewirausahaan, 2021)
The role of MSMEs in the economic development of a country has important implications for increasing income, reducing unemployment, alleviating poverty and economic growth. The Covid-19 pandemic has had a negative impact and threatened the survival of MSMEs. This study aims to analyze the dynamics of the triple helix model by examining the role of each helix: universities, companies, and governments to help MSMEs rise from adversity. This study identifies behavioral profiles in terms of the performance of the triple helix model from the perspective of MSMEs and recognizes key factors for innovation success and competitiveness. The survey involved 134 MSMEs. The analysis method uses SEM-PLS with WarpPLS07. The results of the study indicate that there is a positive influence between the synergy of the government and academia in increasing the innovation and competitiveness of MSMEs. Innovation is able to become a mediator for the synergy of the government and academia in increasing the competitiveness of MSMEs. MSMEs need to be more active and proactive, the role of the government and academics still needs to be improved and coupled with the optimal role of other helixes, especially the community as a strategy to survive and thrive in the Covid-19 pandemic situation.